Assessing the efficacy of infliximab in promoting vascular and mucosal healing in immunoglobulin-resistant kawasaki disease: a meta-analysis - Huiming Cheng (BMC Pediatrics, 2025)
Abstract This meta-analysis investigates the efficacy of infliximab in reducing vascular damage, suppressing inflammation, and promoting mucosal healing in patients with immunoglobulin-resistant Kawasaki Disease (KD). A systematic literature search was conducted in line with PRISMA guidelines across databases (e.g., PubMed, Google Scholar) for studies published between, 2003–2023. While high-dose intravenous immunoglobulin remains the standard treatment for KD, a subset of patients exhibit resistance, necessitating alternative therapeutic strategies. Infliximab, a monoclonal antibody that targets tumor necrosis factor-alpha, presents a promising option for these challenging cases. By modulating the immune response and suppressing inflammation, Infliximab has the potential to alleviate vascular damage and enhance mucosal healing in patients unresponsive to conventional treatments. This study specifically focuses on the impact of Infliximab on healing of vascular damage, as indicated by clinical remission, mucosal healing, and changes in absolute neutrophil counts—a key marker of inflammation. Employing a proportional meta-analysis via the ‘metafor’ function in R, we analyzed data from 857 patients, including 403 events related to mucosal and vascular healing outcomes. Our findings reveal a significant improvement in these healing processes among KD patients treated with Infliximab (Proportion: 0.45, 95% CI: [0.42; 0.48], I² = 87%, p < 0.01), accompanied by a notable reduction in inflammation as evidenced by decreased absolute neutrophil counts (mean difference: 7.67). These results underscore the potential of Infliximab and similar biologic therapies to effectively address the unmet needs of patients with immunoglobulin-resistant KD, offering a viable pathway to mitigate inflammation and enhance mucosal and vascular healing outcomes.